Hydrocephalus due to dilation of Virchow-Robin spaces - RANC, Revista Argentina de Neurocirugia; Morales, Darío; García, Micaela; Demaio, Nicolás; Zamora, León; Asem, Martín; Landaburu, Pablo (Revista Argentina de Neurocirugía, 2024)
Background: Virchow-Robin spaces (VRS) are dilations of perivascular spaces that contain cerebrospinal fluid (CSF) and, sometimes, can cause hydrocephalus.Objectives: to communicate an infrequent case involving a patient afflicted with obstructive hydrocephalus due to dilation of Virchow-Robin spaces.Case description: a 51-year-old female exhibited symptoms of urinary and fecal incontinence, gait disturbances, and cognitive decline over the course of one year. Brain magnetic resonance imaging (MRI) revealed a midbrain multicystic lesion spanning from both thalamus to the pons, T1 and FLAIR hypointense, T2 hyperintense. No enhancement was detected after contrast injection consistent with Virchow-Robin spaces dilation exerting pressure on the Sylvius aqueduct and causing hydrocephalus.Surgery: a ventricular-peritoneal (VP) shunt was implanted resulting in symptom remission. However, shunt revision had to be performed in two occasions with device removal. An endoscopic third ventriculostomy (EVT) was then carried out observing VRS imprint on posterior thalamus and third ventricle floor with Liliequist membrane already fenestrated. Finally, a new contralateral VP shunt was inserted with favorable clinical outcome.Conclusions: dilation of Virchow-Robin spaces may mimic other pathologies with a different prognosis and treatment. When symptomatic, the most effective treatment is CSF diversion either by VP shunt or EVT dependent on the anatomical configuration of third ventricle floor.
Keywords: Endoscopic third ventriculostomy; Hydrocephalus; Ventriculoperitoneal shunt; Virchow-Robin spaces